Composition of the Essential Oil of Endemic Salvia cryptantha (Lamiaceae) Montbret & Aucher Ex Bentham from - Doğan, Gülden; Hayta, Şükrü; Demırpolat, Azıze; Bagcı, Eyüp (My University, 2017)
In this study, the essential oil composition of Salvia cryptantha Montbret & Aucher ex Bentham from Turkey. The qualitative and quantitative essential oil contents of the this species was determined and compared with each other. The chemical composition of essential oils obtained by hydrodistillation of Salvia cryptantha was investigated by GC and GC-MS. The essential oils yield is 0.4 (v/w). Sixty three constituents were comprised the 98.7% of the total essential oil extracted from the Salvia cryptantha. The predominant compounds of Salvia cryptantha were ?determined as 1.8-cineole (21%), camphor (19.1%),? ?-pinene (12.5%), camphene (8.7%).
Keywords: Biyoloji; Bitki Bilimleri